Legal Protection of Rabies Victims in Bali, Which Resulted in The Death of Toddler from a Legal Sociology Perspective - Carwan, Carwan; Lestari, Sari Indah; Febrianty, Yenny; Mahipal, Mahipal (International Journal of Social Service and Research, 2023)
A toddler victim of rabies that causes death violates the right to life, survival and development as outlined in the conception of child protection in the explanation of Law No. 23 of 2002. The problems in this paper are: How is the Legal Sociology Study of the Effectiveness of Rabies Transmission Prevention Regulations, and How is the Legal Protection of Rabies Victims in Bali Causing the Death of Toddlers from a Legal Sociology Perspective? The research method used is Juridical-Empirical. The results showed that the toddler's parents were negligent in the case discussed because the wound was considered small and safe. Hence, the patient (family) was negligent and did not report to the health facility for further treatment. Regarding negligence that causes death, it is explained in Article 359 of the Criminal Code, which reads as follows: "Any person through whose fault (negligence) causes the death of another person shall be punished by a maximum imprisonment of five years or a maximum light imprisonment of one year." From the perspective of Legal Sociology, there is the arbitrary treatment of children carried out by families without paying attention to the child's right to protection following his health condition after being bitten by his pet dog.